HIV-infected individuals who delay, decline, or discontinue antiretroviral therapy: Comparing clinic- and peer-recruited cohorts - Marya eGwadz; Elizabeth eApplegate; Charles eCleland; Noelle Regina Leonard; Hannah eWolfe; Nadim eSalomon; Mindy eBelkin; Marion eRiedel; Angela eBanfield; Lisa eSanfillipo; Andrea eWagner; Donna eMildvan (Frontiers Media S.A., 2014)
A substantial proportion of persons living with HIV/AIDS (PLHA) delay, decline, or discontinue antiretroviral therapy (ART) when it is medically indicated (40-45%), largely African Americans and Latinos/Hispanics. This study explores the feasibility of locating PLHA who are not on ART (PLHA-NOA) through clinics and peer referral; compares the two cohorts on multi-level barriers to ART; and examines readiness to initiate/reinitiate ART, a predictor of treatment outcomes. We recruited adult HIV-infected African American and Latino/Hispanic PLHA-NOA through HIV hospital clinics and peer referral in 2012-13. Participants engaged in structured one-hour assessments with reliable/valid measures on barriers to ART. We found recruitment through peers (63.2%, 60/95) was more feasible than in clinics (36.8%, 35/90). Participants were 48.0 years old and had lived with HIV for 14.7 years on average, and 56.8% had taken ART previously. Most (61.1%) were male and African American (76.8%), and 23.2% were Latino/Hispanic. Peer-recruited participants were older, had lived with HIV longer, were less engaged in HIV care, and were more likely to have taken ART previously. The cohorts differed in reasons for discontinuing ART. Levels of ART knowledge were comparable between cohorts (68.5% correct), and there were no differences in attitudes toward ART (e.g., mistrust), which were in the neutral range. In bivariate linear regression, readiness for ART was negatively associated with physician mistrust (B=-10.4), and positively associated with self-efficacy (B=5.5), positive outcome expectancies (B=6.3), beliefs about personal necessity of ART (B=17.5), and positive internal norms (B=7.9). The present study demonstrates the feasibility of engaging this vulnerable population through peer referral. Peer-recruited PLHA evidence particularly high rates of risk factors compared those in clinics. Interventions to support ART initiation and continuation are sorely needed for both subgroups.